ChemInform Abstract: Multi‐Step Synthesis Strategies Towards 1, 2‐Amino Alcohols with Special Emphasis on Phenylpropanolamines. Issue 25 (5th June 2015) - Sehl, Torsten; Maugeri, Zaira; Rother, Doerte
Abstract: Review: 64 refs.